Wykorzystanie środków finansowych Unii Europejskiej wspierających zrównoważony rozwój obszarów wiejskich w powiecie inowrocławskim - Zawisza, Sławomir; Kostrzak, Dominik (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article presents an analysis of using EU financial means for the purpose of supporting sustainable development of rural areas of the Inowrocław parish in the Kujawsko-pomorskie voivodship. Apart from the analysis of AR and MR documentation a survey was carried out on a group of selected farmers in autumn 2006. The analysis shows that in the examined area almost all possible available sources of financing sustainable development were taken advantage of, except for 2.1 SPO. However, the number of submitted applications suggested medium interest in programmes supporting sustainable development on the side of farmers. The programmes (PROW 6 activity) financing adjustment of farms to the EU standards (PROW 3 activity), supporting agricultural activities in areas with poor farming conditions and agricultural-environmental programs (PROW 4 activity) enjoyed relatively more popularity. Among the agricultural-environmental programs two were of interest for farmers, i.e. water and soil protection and sustainable development. In the population surveyed, 120 farmers, 55%, were interested in the offer of agricultural-environmental programmes. Also 55% were of the opinion that this offer should be extended. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 49-55